2004
DOI: 10.1002/elan.200302930
|View full text |Cite
|
Sign up to set email alerts
|

Electroanalytical and Bioelectroanalytical Systems Based on Metal and Semiconductor Nanoparticles

Abstract: Metal, semiconductor and magnetic particles act as functional units for electroanalytical applications. Metal nanoparticles provide three important functions for electroanalysis. These include the roughening of the conductive sensing interface, the catalytic properties of the nanoparticles permiting their enlargement with metals and the amplified electrochemical detection of the metal deposits and the conductivity properties of nanoparticles at nanoscale dimensions that allow the electrical contact of redox-ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
371
0
8

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 710 publications
(388 citation statements)
references
References 171 publications
1
371
0
8
Order By: Relevance
“…20 In addition, metal nanoparticles could even provide electrochemical reversibility for redox reactions, which is not possible on the bulk metal electrode. 21 Hrapovic et al simply mixed a Pt nanoparticle suspension with single-walled carbon nanotubes (SWCNTs) Nafion suspension to create a glucose biosensor. 15 This study demonstrated that SWCNT provided an excellent support for the Pt nanoparticles for efficient electrical transfer; however, this method resulted in Pt nanoparticle agglomeration.…”
mentioning
confidence: 99%
“…20 In addition, metal nanoparticles could even provide electrochemical reversibility for redox reactions, which is not possible on the bulk metal electrode. 21 Hrapovic et al simply mixed a Pt nanoparticle suspension with single-walled carbon nanotubes (SWCNTs) Nafion suspension to create a glucose biosensor. 15 This study demonstrated that SWCNT provided an excellent support for the Pt nanoparticles for efficient electrical transfer; however, this method resulted in Pt nanoparticle agglomeration.…”
mentioning
confidence: 99%
“…Para avaliar a influência do processo de adsorção, foram usadas duas soluções de 10 -3 mol L -1 de CuSO 4 42 A corrente catódica inicial atribuída ao processo Ic foi associada à redução de íons Cu 2+ a íons Cu + de acordo com a reação 2:…”
Section: Eletrodeposição De Nps-cu Sobre Eletrodos De Ddbunclassified
“…1 Na área eletroquími-ca, particularmente, em eletroanálise, NPs têm sido amplamente utilizadas como nanomatérias funcionais de superfície. Dentre alguns artigos excelentes de revisão publicados na literatura, [2][3][4][5][6] Welch e Compton destacam quatro principais vantagens quanto ao uso de eletrodos modificados com NPs aplicadas em eletroanálise: elevada área superficial efetiva, aumento do transporte de massa, atividade catalítica e controle sobre o microambiente local. 2 Em uma visão mais detalhada, a deposição de NPs resulta em um aumento da rugosidade superficial, que contribui para o aumento da área condutora do eletrodo modificado.…”
Section: Introductionunclassified
“…Nanomaterials were found to have significant roles in a diverse range of analytical methods particularly in sensing applications [7][8][9][10][11] . The increased interest in nanomaterials, especially metallic nanostructures, may be attributed to the often novel physical and chemical properties these nanoparticles display when compared to their bulk counterparts [10,12] .…”
Section: Introductionmentioning
confidence: 99%